The role of the complement system in kidney glomerular capillary thrombosis - Yoshida, Yoko; Nishi, Hiroshi (Frontiers in Immunology, 2022)
The complement system is part of the innate immune system. The crucial step in activating the complement system is the generation and regulation of C3 convertase complexes, which are needed to generate opsonins that promote phagocytosis, to generate C3a that regulates inflammation, and to initiate the lytic terminal pathway through the generation and activity of C5 convertases. A growing body of evidence has highlighted the interplay between the complement system, coagulation system, platelets, neutrophils, and endothelial cells. The kidneys are highly susceptible to complement-mediated injury in several genetic, infectious, and autoimmune diseases. Atypical hemolytic uremic syndrome (aHUS) and lupus nephritis (LN) are both characterized by thrombosis in the glomerular capillaries of the kidneys. In aHUS, congenital or acquired defects in complement regulators may trigger platelet aggregation and activation, resulting in the formation of platelet-mediated thrombi in the kidneys. Because glomerular vasculopathy is usually noted with immunoglobulin and complement accumulation in LN, complement-mediated activation of tissue factors could partly explain the autoimmune mechanism of thrombosis. Thus, kidney glomerular capillary thrombosis is mediated by complement dysregulation and may also be associated with complement overactivation. Further investigation is required to clarify the interaction between these vascular components and develop specific therapeutic approaches.